Bioprosthetic valve thrombosis and degeneration following transcatheter aortic valve implantation (TAVI). Issue 1 (January 2021) - Mirsadraee, S.; Sellers, S.; Duncan, A.; Hamadanchi, A.; Gorog, D.A.
Abstract : Bioprosthetic valve thrombosis (BPVT) is a recognised complication of prosthetic aortic valves and can be found in up to 13% of patients after transcatheter implantation. The mechanism of BPVT is not well known, abnormal flow conditions in the new and native sinuses and lack of functional endothelialisation are suspected causes. BPVT may result in valve dysfunction, possibly related to degeneration, and recurrence of patient symptoms, or remain subclinical. BPVT is best diagnosed at multiphase gated computed tomography (CT) angiography as the presence of reduced leaflet motion (RELM) and hypoattenuating aortic leaflet thickening (HALT). Although CT is used to exclude BPVT in symptomatic patients and those with increased valve gradients, the value of screening and prophylactic anticoagulation is debatable.